Menstrual disorders and related factors in women with multiple sclerosis - Simin Zarabadipour; Leila Amini; Seyed Massood Nabavi; Hamid Haghani (Mashhad University of Medical Sciences, 2018)
Introduction: Multiple sclerosis (MS) is the most common autoimmune disease that often affects women within the reproductive age. Among the common clinical complaints in these women is variety of menstrual disorders. Thus, we aimed to examine menstrual disordersand related factors in women with MS. Methods: A descriptive cross-sectional study was performed among 172 women with MS who visited the Neurology Specialized Clinic in Tehran, Iran, during 2016-2017. The participants filled out a questionnaire consisting of demographic (e.g., age, educational level, economic status, disease duration, vitamin D consumption duration, and Expanded Disability Status Scale [EDSS]) and disease characteristics (age at menstruation, duration of each period, interval between two periods, the amount of bleeding, presence or lack of presence of pain, and menstruation pain score). Data were analyzed by using SPSS version 22 and multiple logistic regression model, Chi-square test, and Spearman correlation coefficient. P-value less than 0.05 was considered significant. Results: Overall, 88 patients (51.2%) experienced irregular menstruation patterns, and 116 patients (67.5%) had some forms of menstruation disorders. Multiple logistic regression reflected statistically significant correlations between disability score (β=0.702, P=0.001), moderate (β=2.561, P<0.001) and high (β=2.730, P<0.001) menstrual bleeding, duration of vitamin D intake (β= -0.187, P=0.048), dysmenorrhea (β=1.246, P=0.006), age of the menarche (β= -0.298, P=0.05) and menstrual pattern (β=1.912, P<0.001) with menstrual disorders. Spearman correlation and Chi-square revealed the significant relationship of menstruation pattern, dysmenorrhea, and amount of bleeding with menstrual disorders, which corroborated the results of regression.  Conclusion: The results of the present study showed that menstrual disorders have high prevalence in women with MS. Our results also indicated that factors such as duration of vitamin D intake, menstrual bleeding, menarche, menstrual pattern, dysmenorrhea, and EDSS affect menstrual disorders.